Fatigue: it's relevance to furniture - Ratnasingam, Jegatheswaran; Perkins, Marius C.; Reid, Hew F. (Springer-Verlag, 1997)
This paper sets out to present the importance of incorporating fatigue related information into the product engineering of furniture constructions. Contrary to commonly accepted thinking, structural failures in furniture very often result from fatigue associated with its repeated use. Hence, performance testing of furniture is needed not only to determine the ultimate static strength of the furniture but also its fatigue strength.